2011
DOI: 10.1143/jjap.50.05fc14
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Ellipsometry Studies of CdS:O Layers for Solar Cells

Abstract: This work reports the results of spectroscopic ellipsometry study of CdS thin films, deposited on glass substrates in the presence of oxygen at room temperature by rf sputtering. The data acquisition, together with the subsequent linear regression analysis to restore dielectric function has been performed over the photon energy range 1.5–5.0 eV. The obtained oxygen-free CdS films and reference bulk CdS have been found to be very much the same regarding their dielectric function spectra. On the other hand, blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…2 It has been reported that the incorporation of O in CdS can result in the formation of nanocrystalline oxygenated CdS, which increases the band gap of the window layer and hence reduces the current loss caused by the absorption of the CdS window layer. [6][7][8][9][10][11] It has also been reported that the presence of O in CdS window layers can help optimize the interdiffusion at CdS/CdTe interface and therefore improve cell performance. 2,12 CdS:O window layers are usually synthesized by the reactive RF sputtering method.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 It has been reported that the incorporation of O in CdS can result in the formation of nanocrystalline oxygenated CdS, which increases the band gap of the window layer and hence reduces the current loss caused by the absorption of the CdS window layer. [6][7][8][9][10][11] It has also been reported that the presence of O in CdS window layers can help optimize the interdiffusion at CdS/CdTe interface and therefore improve cell performance. 2,12 CdS:O window layers are usually synthesized by the reactive RF sputtering method.…”
mentioning
confidence: 99%
“…In the past few years, several groups have reported that the band gap of CdS can be tuned by incorporating oxygen during the sputter deposition. [6][7][8][9][10] Even a small O 2 /(O 2 þ Ar) ratio ($2%) has been reported as sufficient to produce nanocrystalline CdS films with room temperature (RT) sputtering. Therefore, in most reported high efficiency CdTe thin-film solar cells, the CdS:O window layers are deposited at RT by RF sputtering.…”
mentioning
confidence: 99%
“…The new CdTe cells used CdS:O window layers, sputtered at room temperature (RT) using a 5% oxygen ambient. The oxygenated CdS is supposed to improve the blue response because of the enlarged bandgap . The solar cells were then completed with our standard CdCl 2 activation and CuSCN/Au or Cu/Au back contacts.…”
Section: Resultsmentioning
confidence: 99%